Effect of Water Clover (Marsilea crenata) Ethanol Extracts on Follicle and Oocyte Diameter of Goat: In Vitro Study - Widhaningrum, Siska Nanda; Putranto, Septiawan; Rahayu, Sri; Ciptadi, Gatot (Graduate School, Universitas Brawijaya, 2020)
Water clover (Marsilea crenata) is one of the herbal plants that has been using in alternative medicine. It possesses pharmacologically active compounds like flavonoid, which has cellular activities such as antioxidant and estrogenic activity. This study aimed to evaluate the impact of water clover ethanol extract (WCE) at different concentrations on the growth of follicles and oocytes based on follicles and oocytes diameter, respectively, after six days of culture. This experimental study used 24 isolated antral follicles (2.5-3.2 mm), which were randomly divided into four groups including control (without supplemented WCE) and experimental groups that supplemented with different concentrations of WCE (21.6, 43.2, and 86.4 µg ml-1) in culture medium for six days culture. The diameter of follicles was measured on days 0, 3, and 6. Additionally, oocytes diameter was also measured on day 6. The results indicate that the mean diameter of antral follicles and oocyte diameter of WCE 43.2 µg ml-1 was significantly increase compared to the other groups (P≤0.05). According to our results, WCE exerts its effect on the growth of the antral follicle and oocyte based on follicles and oocytes diameter respectively in a dose-dependent manner after six days of the antral follicle cultured. Keywords: antral follicle, flavonoid, in vitro, oocyte, water clover.